2008
DOI: 10.2151/jmsj.86.719
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Inertia-Gravity Waves in the Middle Stratosphere Based on Intensive Radiosonde Observations

Abstract: An intensive observation of the stratosphere has been made using 10 radiosondes every 3 h for the time period of 11−12 May 2006 at Shigaraki, Japan (34. 85°N, 136.11°E). Horizontal wind and temperature data were successfully obtained with high accuracy in the height region up to about 36 km. The sampling time intervals are 2 s corresponding to a nominal vertical resolution of about 10 m.Two packets of wavelike fluctuations whose phases propagate downward are detected around a height of 34 km (hereafter referre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 27 publications
0
22
0
Order By: Relevance
“…The elliptical shape of the hodograph is recognized to be a signature of IGWs (Tateno & Sato 2008). The main ellipse is turning clockwise with height indicating a vertically upward propagation in the region 0.4 < z < 1.8, delimiting the location of IGW activity pointed out in figure 12.…”
Section: Polarization Relationsmentioning
confidence: 82%
See 2 more Smart Citations
“…The elliptical shape of the hodograph is recognized to be a signature of IGWs (Tateno & Sato 2008). The main ellipse is turning clockwise with height indicating a vertically upward propagation in the region 0.4 < z < 1.8, delimiting the location of IGW activity pointed out in figure 12.…”
Section: Polarization Relationsmentioning
confidence: 82%
“…Many observational studies on gravity waves have been conducted using time series of velocity profiles, that provide evidence and characteristics of the waves such as group velocity and the energy source (Leaman & Sanford 1975;Thompson 1978;Thomas, Worthingthon & McDonald 1999;Tateno & Sato 2008). Tateno & Sato (2008) studied the source of IGW packets in the middle stratosphere using a ray-tracing method and the results indicated that IGWs packets were generated in the vicinity of the unbalanced westerly jet due to spontaneous adjustment processes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to these isolated regions, negativeρu w is distributed zonally along the eastward jet. These effects may be due to the gravity waves excited by spontaneous adjustment around jet-frontal systems (O'Sullivan and Dunkerton, 1995;Kawatani et al 2004;Zhang, 2004;Plougonven and Snyder, 2007;Sugimoto et al 2008;Sato and Yoshiki, 2008;Tateno and Sato, 2008). In the summer (Northern) hemisphere, strong positiveρu w is observed only in the Indian and African monsoon regions.…”
Section: Seasonal Variation Of Gravity Waves and Their Sourcesmentioning
confidence: 99%
“…Reid et al 1994, Chane-Ming et al 2000, Tateno and Sato, 2008. Ultra-thin-film high-altitude balloons that can attain an altitude of about 50 km (Matsuzaka et al 2000) have been used since 2004.…”
Section: Introductionmentioning
confidence: 99%